The Role of Glucagon in the Acute Therapeutic Effects of SGLT2 Inhibition - Hædersdal, Sofie (Diabetes, 2020)
Sodium–glucose cotransporter 2 inhibitors (SGLT2i) effectively lower plasma glucose (PG) concentration in patients with type 2 diabetes, but studies have suggested that circulating glucagon concentrations and endogenous glucose production (EGP) are increased by SGLT2i, possibly compromising their glucose-lowering ability. To tease out whether and how glucagon may influence the glucose-lowering effect of SGLT2 inhibition, we subjected 12 patients with type 2 diabetes to a randomized, placebo-controlled, double-blinded, crossover, double-dummy study comprising, on 4 separate days, a liquid mixed-meal test preceded by single-dose administration of either 1) placebo, 2) the SGLT2i empagliflozin (25 mg), 3) the glucagon receptor antagonist LY2409021 (300 mg), or 4) the combination empagliflozin + LY2409021. Empagliflozin and LY2409021 individually lowered fasting PG compared with placebo, and the combination further decreased fasting PG. Previous findings of increased glucagon concentrations and EGP during acute administration of SGLT2i were not replicated in this study. Empagliflozin reduced postprandial PG through increased urinary glucose excretion. LY2409021 reduced EGP significantly but gave rise to a paradoxical increase in postprandial PG excursion, which was annulled by empagliflozin during their combination (empagliflozin + LY2409021). In conclusion, our findings do not support that an SGLT2i-induced glucagonotropic effect is of importance for the glucose-lowering property of SGLT2 inhibition.